A cross-cultural investigation of the effects of organisational culture on employee motivation and commitment, and its impact on performance within an international non-profit organisation - Gill, Jaspreet (2017)
The purpose of this dissertation was to investigate into the unexplored topic of the effects of organisational culture on employee motivation and commitment, and its overall impact on performance; as well as this, the dissertation undergoes a cross-cultural comparison. The research is based on an ethnography conducted in both the UK and India. This dissertation shows how culture plays an integral role in motivating employees and keeping them committed to a non-profit organisation, which has no monetary rewards or other incentives; the drive to work for a non-profit organisation, specifically Your Seva, stems from religion and culture, where employees felt it was their duty as a member of the Sikh community to be committed. It was particularly interesting to see how organisational culture remained consistent, even when operating within two completely different countries – motivational functions and reasons to commit to the non-profit organisation were similar in both settings.